In Search of A Giffen Input: A Comprehensive Analysis of The Wold-Juréen (1953) Production Function - SPROULE, Robert (Journal of Mathematical Economics and Finance; Vol 8 No 2 (2022): JMEF, Volume VIII, Issue 2(15), Winter 2022, 2022)
The Wold-Juréen (1953) utility function serves as an exemplar of those utility functions which have the potential to yield a Giffen good. As such, this utility function has contributed much to the overall development of consumer theory. Because of the said success of the Wold-Juréen (1953) utility function, it seems only natural to ask this: can the Wold-Juréen (1953) functional form also serve as an ex- emplar of those production functions which have the potential to yield a Giffen factor? Since our review of the literature suggests that no such question has ever been posed, therein lies the purpose of the present paper.